Core–Shell Hydrogel Microcapsules for Improved Islets Encapsulation. Issue 5 (3rd December 2012) - Ma, Minglin; Chiu, Alan; Sahay, Gaurav; Doloff, Joshua C.; Dholakia, Nimit; Thakrar, Raj; Cohen, Joshua; Vegas, Arturo; Chen, Delai; Bratlie, Kaitlin M.; Dang, Tram; York, Roger L.; et al.
<x xml:space="preserve">Abstract</x> Islets microencapsulation holds great promise to treat type 1 diabetes. Currently used alginate microcapsules often have islets protruding outside capsules, leading to inadequate immuno‐protection. A novel design of microcapsules with core–shell structures using a two‐fluid co‐axial electro‐jetting is reported. Improved encapsulation and diabetes correction is achieved in a single step by simply confining the islets in the core region of the capsules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>